DEVELOPMENT, CHALLENGES, AND SOLUTIONS IN FINE ART CLASSES WITHIN HIGHER EDUCATIONAL INSTITUTIONS - Baratbayev Batir Mamadjonovich (Galaxy International Interdisciplinary Research Journal, 2023)
Fine art classes in higher educational institutions play a critical role in nurturing future artists, providing them with theoretical knowledge, technical skills, and a platform to explore creative expressions. However, these programs face certain challenges that hinder the optimal growth and development of aspiring artists. This article discusses the development of fine art classes, highlights the problems encountered, and proposes possible solutions to enhance the effectiveness and efficiency of these programs.